2018
DOI: 10.1111/dom.13443
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel herbal formulation for weight loss demonstrated in a 16‐week randomized, double‐blind, placebo‐controlled clinical trial with healthy overweight adults

Abstract: The unique herbal extract blend LI85008F, combined with modest calorie restriction and physical activity, is well tolerated, safe, and effective for weight management in overweight men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
3
20
1
Order By: Relevance
“…From day 29, the start of the supplementation phase, the rats received an oral gavage of 0.5% Carboxymethylcellulose Sodium (CMC) alone (G1 and G2) or combined with the selected doses of LI85008F (G3 and G4). The low dose of the herbal blend tested in the present study was approximately equivalent to the clinical dose of LI85008F [10,11].…”
Section: Animal Care and Experimental Designmentioning
confidence: 88%
See 4 more Smart Citations
“…From day 29, the start of the supplementation phase, the rats received an oral gavage of 0.5% Carboxymethylcellulose Sodium (CMC) alone (G1 and G2) or combined with the selected doses of LI85008F (G3 and G4). The low dose of the herbal blend tested in the present study was approximately equivalent to the clinical dose of LI85008F [10,11].…”
Section: Animal Care and Experimental Designmentioning
confidence: 88%
“…Subsequently, two clinical studies have demonstrated that LI85008F supplementation significantly reduced body weight (BW), along with BMI in overweight and obese human subjects. LI85008F also improved the lipid profile and adiponectin level in serum, compared with the placebo [9][10][11]. Two exciting findings in the earlier clinical studies were enhanced intracellular fat breakdown in the LI85008F treated 3 T3-L1 fat cells, and increased serum adiponectin level in LI85008F supplemented participants.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations